Epithelial–mesenchymal transition in the formation of hypertrophic scars and keloids. Issue 12 (20th May 2019) - Yuan, Feng‐Lai; Sun, Zi‐Li; Feng, Yi; Liu, Si‐Yu; Du, Yong; Yu, Shun; Yang, Ming‐Lie; Lv, Guo‐Zhong
Abstract: Abnormal wound healing is likely to induce the formation of hypertrophic scars and keloids, which leads to dysfunction, deformity, and mental problem in the patients. Despite the advances in prevention and management of hypertrophic scar and keloids, the mechanism underlying scar and keloid formation has not been fully elucidated. Recent insights into the role of the epithelial–mesenchymal transition (EMT) in development, wound healing, stem cell regulation, fibrosis, and tumorigenesis have increased our understanding of the pathophysiology of hypertrophic scarring and keloids and suggested new therapeutic targets. This review summarizes recent progress in the elucidation of the role of EMT in physiologic wound healing and pathologic scar formation. This knowledge will facilitate an understanding of EMT roles in scar formation and shed new light on the modulation and potential treatment of hypertrophic scars and keloids.